Single Cell Transcriptomics Reveal Abnormalities in Neurosensory Patterning of the Chd7 Mutant Mouse Ear - Durruthy-Durruthy, Robert; Sperry, Ethan D.; Bowen, Margot E.; Attardi, Laura D.; Heller, Stefan; Martin, Donna M. (Frontiers in Genetics, 2018)
The chromatin remodeling protein CHD7 is critical for proper formation of the mammalian inner ear. Humans with heterozygous pathogenic variants in CHD7 exhibit CHARGE syndrome, characterized by hearing loss and inner ear dysplasia, including abnormalities of the semicircular canals and Mondini malformations. Chd7Gt/+ heterozygous null mutant mice also exhibit dysplastic semicircular canals and hearing loss. Prior studies have demonstrated that reduced Chd7 dosage in the ear disrupts expression of genes involved in morphogenesis and neurogenesis, yet the relationships between these changes in gene expression and otic patterning are not well understood. Here, we sought to define roles for CHD7 in global regulation of gene expression and patterning in the developing mouse ear. Using single-cell multiplex qRT-PCR, we analyzed expression of 192 genes in FAC sorted cells from Pax2Cre;mT/mGFP wild type and Chd7Gt/+ mutant microdissected mouse otocysts. We found that Chd7 haploinsufficient otocysts exhibit a relative enrichment of cells adopting a neuroblast (vs. otic) transcriptional identity compared with wild type. Additionally, we uncovered disruptions in pro-sensory and pro-neurogenic gene expression with Chd7 loss, including genes encoding proteins that function in Notch signaling. Our results suggest that Chd7 is required for early cell fate decisions in the developing ear that involve highly specific aspects of otic patterning and differentiation.